The Surface Mining Of Bauxite And Its Impacts To The Natural Environment Of Northeastern Ghiona - A. Mertzanis (Society for Mining, Metallurgy & Exploration, 2006)
The way and methods used for the surface mining of bauxite until the end of the twentieth century in the area of Ghiona, resulted in a significant burden to the natural environment, especially in the cases where it covered extended parts of forests and forest areas as well as important geomorphological formations. The impacts from the surface mining of bauxite which in fact constitute the object of this study relate mainly to the interruption of the natural continuity of the land relief and the alteration of the natural geomorphological activities and are due to: a) the alternating excavations with fronts of great heights, b) the depositions of large volumes of waste materials which originate from the revealing of the ore and c) the dense road network constructed in order to get access to the mine locations.